1996
DOI: 10.1046/j.1365-2362.1996.2210562.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalitis and the adrenocortical response of resistant and susceptible mice to acute murine cytomegalovirus infection

Abstract: Murine cytomegalovirus (MCMV) induces adrenalitis in BALB/c mice but does not compromise adrenal function, assessed by levels of circulating adrenocorticotropic hormone (ACTH) and by the response to challenge with synthetic ACTH. Levels of corticosterone increased 2 days after infection in mice of this strain, consistent with previously established interactions between mediators of acute inflammation and activation of the hypothalmus-pituitary-adrenal axis. Moreover, an adrenocortical response was critical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…This may reflect genetic differences between both strains, since the animals were kept in the same animal facilities and were subjected to similar experimental conditions. In support of this possibility, Balb/c mice, compared to C57Bl/6J mice, have been reported to respond to certain types of stress (Lu et al 1998) and virus (Price et al 1996) with stronger stimulation of the HPA axis. We and others (Leite de Moraes et al 1991, Roggero et al 2002, Mantuano-Barradas et al 2003 have shown that during the acute phase of T. cruzi infection, there is a marked thymus atrophy, mainly characterized by the loss of CD4 C CD8 C cells.…”
Section: Discussionmentioning
confidence: 92%
“…This may reflect genetic differences between both strains, since the animals were kept in the same animal facilities and were subjected to similar experimental conditions. In support of this possibility, Balb/c mice, compared to C57Bl/6J mice, have been reported to respond to certain types of stress (Lu et al 1998) and virus (Price et al 1996) with stronger stimulation of the HPA axis. We and others (Leite de Moraes et al 1991, Roggero et al 2002, Mantuano-Barradas et al 2003 have shown that during the acute phase of T. cruzi infection, there is a marked thymus atrophy, mainly characterized by the loss of CD4 C CD8 C cells.…”
Section: Discussionmentioning
confidence: 92%
“…This increased mortality following adrenalectomy was correlated with increases in levels of the cytokines IFN , TNF and IL-6 (Ruzek et al 1999). In another study, adrenalectomy of BALB/c, but not C57BL/6, mice increased the mortality rates from MCMV virus (Price et al 1996). In the study by Price et al 4 10 4 pfu (plaque-forming units) MCMV virus was used, and 85% of the adrenalectomized C57BL/6 mice survived (Price et al 1996).…”
Section: Viral Infectionsmentioning
confidence: 95%
“…The kinetics of glucocorticoid release is both virus-specific and specific to the phase of the response, and is also influenced by the route of exposure. The murine cytomegalovirus (MCMV) (Price et al 1996, Ruzek et al 1997, Pearce et al 2001, lymphocytic choriomeningitis virus (LCMV) , Pearce et al 2001 and poly (I:C) (a synthetic viral analog) induced increases in glucocorticoid levels (Ruzek et al 1997, Pearce et al 2001. Furthermore, MCMV virus and poly (I:C) have been shown to induce glucocorticoid release through an interleukin (IL)-6-dependent pathway (Ruzek et al 1997).…”
Section: Viral Hpa Axis Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12] Previous work by our group and others has demonstrated that removal of glucocorticoids (via adrenalectomy (ADX)) during viral infection is associated with elevations in plasma and tissue concentrations of proinflammatory cytokines and renders animals more susceptible to septic shock and death. [13][14][15] In addition, in the case of infection with murine cytomegalovirus (MCMV), a cytopathic virus that induces an early natural killer cell-mediated, anti-viral defense accompanied by elevations in plasma TNF-alpha, IL-1 and IL-6, 15 the increased death rate in adrenalectomized, MCMV-infected, animals can be reversed by glucocorticoid replacement. 15 Previous studies also have shown that the MCMV-induced corticosterone response, which parallels peak plasma cytokine concentrations and occurs around 36 h after infection, is dependent on IL-6.…”
Section: Introductionmentioning
confidence: 99%